Intervensi Ergonomi untuk Menurunkan Beban Kerja pada Operator Lantai Produksi Bisnis Unit South Copper Rod - Kevin Salsia; Dian Mardi Safitri; Ranny Dwi Anggraini (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2018)
Workload is a set or number of work activities that must be completed by an organizational unit. Activities carried out by humans will cause physical fatigue and psychological (mental) fatigue. Workload measurement is used to refine the size of the workload experienced by someone in carrying out activities, and to increase the level of productivity in work. This study aims to reduce the workload on the production floor. Based on research conducted by interviews and (surveys) found symptoms of excessive workload. The workload found is in the form of work stress and fatigue due to excessive physical activity. Measurement of mental workload using the NASA-TLX method and measurement of physical workload using the cardiovascular load method. The stages of the study were continued by finding the correlation between workload and reaction time. The results of the correlation of physical workload get a value of 0.334 which means